ANALISIS SKEMA PROYEK KERJASAMA PEMERINTAH DAN BADAN USAHA DALAM SISTEM PENYEDIAAN AIR MINUM END TO END: Analysis of Goverment and Business Entity Cooperation Project Schemes in End to End Drinking Water Supply System - Fauziyah, Intan Diana (Fakultas Hukum, Universitas Trisakti, 2024)
Providing drinking water is a crucial aspect in efforts to improve community welfare. Collaboration between government and business entities has become a common approach in developing drinking water infrastructure. This research aims to analyze cooperation project schemes with the government and business entities end to end drinking water supply system. This research aims to analyze the implementation of the end-to-end SPAM project scheme and its conformity with the provisions regulated in PP Number 122 of 2015, especially Article 56. One important aspect of this regulation is Article 56, which regulates administrative sanctions for SPAM operators who does not comply with his obligations. The analysis results show that the suitability of the end to end SPAM project scheme with Article 56 PP Number 122 of 2015 depends on the extent to which the project complies with all the obligations and provisions stipulated in the regulation. Thus, this research provides in-depth insight into the implementation of the SPAM project scheme in the context of regulations in force in Indonesia.